Weaknesses of MMT as a guide to development policy - Adam Aboobaker; Esra Nur Ugurlu (University of Massachusetts, Department of Economics, 2020)
This paper addresses the limitations of Modern Money Theory (MMT) as a guide to development policy. We explore two central questions on this topic: whether MMT policies 1) ought to be implemented in low- and middle-income economies and 2) can be implemented. In relation to the first question, we argue that the MMT literature mischaracterizes the essence of the development challenge for low- and middle-income economies. Our argument is that the chief long-run growth challenge faced by developing countries concerns structural transformation rather than general aggregate demand insufficiency. We use several formal representations of the consumption-investment trade-off in growth theory, found in the Harrod-Domar growth model, Kalecki's 1963 growth model, and Feldman-Mahalanobis model, to illustrate this point. Concerning the second question, we argue that even if MMT had the correct diagnosis of the principal growth challenge faced by developing countries, its chief policy recommendations would likely be counter-productive if implemented outside of select advanced economies. We draw from the international economics literature on currency hierarchy and exchange rate volatility to illustrate this point.
Keywords: O10; O41; E0; B0; 330; MMT; structural change; macro policy; growth models; history of economic thought